A revolutionary change in health care: Doctorola Limited a view into quiet health tech revolution - Anwar, Md. Sayed (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.